Labour market deregulation and gender wage equity: Evidence from WA. - Crockett, Geoffrey; Preston, Alison (Curtin University of Technology, 1999)
It is widely predicted labour market deregulation will adversely impact onfemale earnings. The evidence for Australia has, so far, been mixed.Content analysis of agreements suggests that equal employmentopportunities are been compromised, but aggregate wage data showsthat this has had no discernible effect on the gender wage gap. In thispaper we focus specifically on Western Australia and show that whereradical industrial relations reforms have been introduced, gender wageequity has, indeed, been compromised. Western Australia 'leads the way'in industrial relations reforms. Many reforms recently proposed at thefederal level have already been implemented in Western Australia. Thelatter thus provides a window on future developments with respect togender wage equality ... and the outlook is not good.